ТАЛАБАЛАРНИНГ ЎҚУВ-БИЛИШ ФАОЛИЯТИНИ БОШҚАРИШ МОДЕЛЛАРИ - Бектурсынова, Л.Х. (SCIENCE and SOCIETY, 2018)
In the article there have been analyzed the stages and pedagogical-psychologic peculiarities of the models of managing students‘ learning cognitive activity.
Keywords: талаба; билиш; ўқув фаолияти; бошқариш; модел; консультант; тьютор; модератор; фасилитатор